1990
DOI: 10.1002/dc.2840060403
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cytologic diagnosis: Evaluation of 370 consecutive intraoperative cytologies

Abstract: Three-hundred and seventy intraoperative cytologies are presented and compared with synchronously performed frozen sections. Cytologic smears and frozen sections were misinterpreted in 1.6% and 0.8% of cases, respectively; the rate of diagnostic errors between the two techniques is comparable given the lack of experience with intraoperative cytology at the beginning of the study. Intraoperative cytology is a suitable technique for a variety of lesions, but it is most helpful in the field of neuro-oncological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 13 publications
1
29
0
1
Order By: Relevance
“…In our study, the overall diagnostic accuracy of squash cytology was 95% when compared with histology as the gold standard, which correspond to or even better than some of the studies [11][12][13]. Few studies also compared results of squash cytology with frozen section and concluded that the accuracy of cytology was as good as frozen section [14][15][16]. In fact, studies have shown that the use of intra-operative cytology has great value in providing diagnostic information when frozen section was equivocal or when frozen-section evaluation could not be done [e.g., excessively small sample] [17].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In our study, the overall diagnostic accuracy of squash cytology was 95% when compared with histology as the gold standard, which correspond to or even better than some of the studies [11][12][13]. Few studies also compared results of squash cytology with frozen section and concluded that the accuracy of cytology was as good as frozen section [14][15][16]. In fact, studies have shown that the use of intra-operative cytology has great value in providing diagnostic information when frozen section was equivocal or when frozen-section evaluation could not be done [e.g., excessively small sample] [17].…”
Section: Resultssupporting
confidence: 75%
“…Further, elimination of freezing artifact [12] and reduced cryostat contamination from potentially infected tissue make squash cytology superior over frozen section [10]. some authors suggest that cytological preparation provides better morphology than frozen section with even minute biopsy material [11,14,19]. Thus, though frozen section was considered complementary to squash cytology [5], the latter alone can guide neurosurgeon during intra-operative period in many of the institutes where frozen section is not performed routinely for various logistic and technical reasons [9].…”
Section: Resultsmentioning
confidence: 99%
“…[5]Since then it has been used by many investigators to evaluate sentinel node in breast cancer [3], mucosal cut margins in oral cancer [6] and as an adjunct to intraoperative frozen section [7].…”
Section: Discussionmentioning
confidence: 99%
“…O exame microscópico per-operatório, seja pela técnica do esfregaço ou pela realização de cortes congelados, é amplamente utilizado desde a sua introdução no início do século 20 (9,24,37) . As vantagens do exame citológico (esfregaço) sobre o corte congelado incluem a maior rapidez (em geral é realizado em cerca de 5 minutos), o menor custo, pois não necessita de aparelhagem para corte nem de técnico especializado, e, em se tratando de suspeita de lesões infecciosas, evita a contaminação do criostato (15,27,31) . No caso específico das neurocirurgias, onde as amostras são em geral escassas e diminutas, o exame citológico apresenta mais vantagens em relação ao corte congelado, pois requer menor quantidade de material, permitindo a preservação de tecido para inclusão em parafina e para a realização de estudo imuno-histoquímico.…”
Section: Introductionunclassified